Introductory statistical thermodynamics - Dalarsson, M. (Mirjana); Dalarsson, N. (Nils); Golubovic, L. (Leonardo) (Academic Press, 2011)
Introductory Statistical Thermodynamics is a text for an introductory one-semester course in statistical thermodynamics for upper-level undergraduate and graduate students in physics and engineering. The book offers a high level of detail in derivations of all equations and results. This information is necessary for students to grasp difficult concepts in physics that are needed to move on to higher level courses. The text is elementary, self contained, and mathematically well-founded, containing a number of problems with detailed solutions to help students to grasp the more difficult theoretical concepts. Beginning chapters place an emphasis on quantum mechanics Includes problems with detailed solutions and a number of detailed theoretical derivations at the end of each chapter Provides a high level of detail in derivations of all equations and results.